To use the distributive property to remove the parentheses from the expression \((1 - 6x + 3u)(-6)\), you need to multiply each term inside the parentheses by \(-6\).
Here’s how to do it step-by-step:
- Distribute \(-6\) to each term inside the parentheses.
\[ = -6 \cdot 1 + (-6) \cdot (-6x) + (-6) \cdot 3u \]
- Calculate each multiplication:
- \(-6 \cdot 1 = -6\)
- \(-6 \cdot (-6x) = 36x\)
- \(-6 \cdot 3u = -18u\)
- Put it all together:
\[ -6 + 36x - 18u \]
So, the expression without parentheses is:
\[ 36x - 18u - 6 \]